Optimization of Liquid Smoke Products Made from Rubberwood with Pyrolysis Method - Bazlina Dawami Afrah; M. Ihsan Riady; Lia Cundari; Muhammad Andzar Rizan; Jihan Utami; Siti Istiani Pratiwi; Muhammad Yori Pratama (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
A large amount of rubberwood waste in Indonesia is caused by abundant rubberwood production. However, the utilization of rubberwood waste has not been optimized in Indonesia. One of the efforts to utilize rubberwood waste is to process it into liquid smoke. Liquid smoke is the dispersion of smoke vapor in water. The raw material used in this research is rubberwood. This study aimed to determine the quality of liquid smoke after purification by knowing the volume, density, pH, viscosity, yield, and phenol content using rubberwood as raw material and the pyrolysis method. The pyrolysis process is purified by distillation based on differences in boiling points. This research is divided into two stages of distillation, namely low grade purified liquid smoke and high grade purified liquid smoke. The analysis results will follow the quality standards of Japanese liquid smoke. The results show that the best liquid smoke from this research is liquid smoke with a pyrolysis time of 3 hours because it meets Japanese liquid smoke quality standards.